Liver chemoembolization of hepatocellular carcinoma using TANDEM® microspheres. (28th June 2018) - Delicque, Julien; Guiu, Boris; Boulin, Mathieu; Schwanz, Heidi; Piron, Lauranne; Cassinotto, Christophe
Transarterial chemoembolization (TACE) combines intra-arterial delivery of a chemotherapeutic agent with selective embolization to obtain a synergistic effect. TACE is recognized as the standard treatment of hepatocellular carcinoma patients at an intermediate stage. If conventional TACE, defined as the injection of an emulsion of a drug with ethiodized oil, still has a role to play, the development of drug-eluting beads has allowed many improvements and optimization of the technique. TANDEM ® microspheres are second-generation drug-loadable microspheres. This device raised a special interest due to its tightly calibrated spherical microspheres, with small sizes down to 40 μm available. In this review, we describe the technical characteristics of these microspheres, analyze the scientific literature and hypothesize on the future perspectives.